Summary of telephone conversation with Miss Brooks
1938-11-25 042-0039-001 Telephone conversation. 25th November, 1938 Miss Brooks telephoned, referred to Sir Daniel Stevenson's letter, and asked whether Mr. Tewson could give her an appointment this afternoon or Saturday morning. She is starting for Spain Saturday mid-day. On Mr. Tewson's instructions I explained that he was very much occupied this afternoon, and would not be in the office to-morrow, Saturday. He was afraid he could not fit in an interview, but if she had anything important she wished to tell him I could take a message. She said no, there was nothing important to tell. She only wanted a chat with him. C.S.B. 292/946/42/39(i)